ANALISIS SISTEM PENGENDALIAN INTERNAL TERHADAP PEMBERIAN DAN PELUNASAN PIUTANG PADA KOPERASI PEGAWAI NEGERI (KPN) BAHTERA BITUNG - Lahope, Wendy Hillari; Runtu, Treesje; Wangkar, Anneke (Universitas Sam Ratulangi, 2018)
Internal controls should be supported by the presence of control components which include: control environment, control activities, risk assessment, information and communication, and monitoring. All of these will support the achievement of internal control objectives. The purpose of this study is to determine whether the internal control system on the provision and repayment of receivables at the Cooperative Employees (KPN) Bahtera Bitung is in accordance with the theory of COSO. The method used is descriptive method. Based on the results of research conducted by researchers, it can be concluded that the internal control system in the cooperative is still less effective, due to the absence of division of tasks or the granting of authority and responsibility, and bad debts are still common in the Employees Cooperative (KPN) Bahtera Bitung.Keywords : Internal Control System, Accounts Receivable